Розвиток українсько-угорських дипломатичних відносин у кінці ХХ століття - Світлана Мишко; Лізак Катерина; Svitlana Myshko; Kateryna Lizak; Lizák Katalin (ДВНЗ «УжНУ», 2020)
Резюме. У статті розглядається становлення та розвиток дипломатичних відносин між Україною та Угорщиною – країною, яка першою визнала Україну незалежною державою, що привело до відкриття дипломатичних місій та підписання базового договору між цими країнами. Автори підкреслюють, що українська двостороння дипломатія новітньої доби розпочинається саме з Угорщини, та аналізують перші етапи розбудови українсько-угорських відносин. Наголошу- ється, що цей період характеризується динамічним розвитком, активною співпрацею та прагненням до встановлення і підтримки дружніх добросусідських відносин.

Abstract. Diplomatic relations are considered to be a decisive factor indicating the level of good neighbourly relations between the states in a particular region. For that purpose we consider the analysis of the diplomatic relations between Ukraine as an independent state and the Republic of Hungary – with a special shift on the events during the period from 1990 to 2000 – to be vital for the understanding of the present and future relations between these two nations. The study aims at providing a brief overview of the establishment and development of the international relations between Ukraine, the largest European country and one of its seven neighbours, namely, Hungary. Similarly, it includes information on the background events underlying the significance of these relations as well as describes the changes in the character of the relations between the two aforementioned states. According to the objectives of the research, we used general scientific and special research methods that provided a holistic approach to solving the problem, namely, methods of critical analysis and synthesis, comparison, generalization and analogy. It may be concluded that the beginning of the 90s witnessed almost perfect-like Ukrainian-Hungarian diplomatic relations whereas the 21st century revealed certain problematic issues. However, both the Ukrainian and Hungarian governments and their people have always strived for a friendly partnership, establishing and strengthening their relations.
The development of Ukrainian-Hungarian diplomatic relations at the end of the twentieth century
Keywords: дипломатія; незалежна держава; інтеграція; двосторонні відносини; переговори; посольство; дипломатичне представництво